Evaluation of the Successful Implementation of the SIMARDI Using the Technology Acceptance Model (TAM) - R Rosda; Muhammad Wali; I Imilda (CV. Media Digital Publikasi Indonesia, 2023)
The purpose of this study is to evaluate acceptance by archivists of the SIMARDI archive application developed specifically for archive management and classification of archives from public institutions and private individuals. The application provides systematic and structured processing capabilities that enable archivists to effectively manage records, control high-level file management systems, and track archived data quickly and accurately. The methodology used in this study is the Technology Adoption Model (TAM). It has been shown to be effective in describing and predicting user acceptance of technology. The study was conducted by collecting data through questionnaires completed by 30 SIMARDI application users. This questionnaire was designed to measure archivist perceptions of the SIMARDI program and the factors that influence their use of the application. The results showed that archivists positively accepted the SIMARDI application. Usability reached 74%, usability 72.57%, and technology acceptance 73.80%. The study recommends that SIMARDI application developers focus on improving usability variables that score poorly. The results of this research will help increase user adoption not only for government and private organizations looking to implement efficient and user-friendly filing systems, but also for application developers